2008
DOI: 10.1111/j.1753-6405.2008.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Did it fall or was it pushed? The contribution of trends in established risk factors to the decline in premature coronary heart disease mortality in New Zealand

Abstract: Objective: To estimate the contribution of trends in three risk factors -systolic blood pressure (SBP), total blood cholesterol (TBC) and cigarette smoking -to the decline in premature coronary heart disease (CHD) mortality in New Zealand from 1980-2004. Method: Risk factor prevalence data by 10-year age group (35-64 years) and sex was sourced from six national or Auckland regional health surveys and three population censuses (the latter only for smoking). The data were smoothed using two-point moving averages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Capewell, Beaglehole, and colleagues (17) applied the IMPACT model to data from New Zealand for the period from 1982 to 1993 and estimated that treatments accounted for ∼46% of the decline in CHD mortality and that changes in risk factors accounted for ∼54% (smoking 30%, cholesterol 12%, and blood pressure 8%). Using a different methodology, Tobias and colleagues suggested that ∼80% of the decline in CHD mortality from 1980 to 2004 could be explained by secular changes in smoking, SBP, and total cholesterol, attributing most of the effect of blood pressure and total cholesterol to improvements in lifestyle, particularly diet, because rates of use of antihypertensive medications and cholesterollowering medications were low into the 1990s (117).…”
Section: Explaining the Decline In Chd Mortality Elsewhere: Changes Imentioning
confidence: 99%
“…Capewell, Beaglehole, and colleagues (17) applied the IMPACT model to data from New Zealand for the period from 1982 to 1993 and estimated that treatments accounted for ∼46% of the decline in CHD mortality and that changes in risk factors accounted for ∼54% (smoking 30%, cholesterol 12%, and blood pressure 8%). Using a different methodology, Tobias and colleagues suggested that ∼80% of the decline in CHD mortality from 1980 to 2004 could be explained by secular changes in smoking, SBP, and total cholesterol, attributing most of the effect of blood pressure and total cholesterol to improvements in lifestyle, particularly diet, because rates of use of antihypertensive medications and cholesterollowering medications were low into the 1990s (117).…”
Section: Explaining the Decline In Chd Mortality Elsewhere: Changes Imentioning
confidence: 99%
“…A growing body of evidence suggests that 45%-70% of the recent decline in CHD mortality could be attributed to decrease in risk factors [2,4,6,18,19]. Furthermore Taylor et al, in Australia and New Zealand, using a different methodology, estimated that the decline in risk factors could explain 74% of the decline in CHD mortality in men, and 84% in women [7,8,20].…”
Section: Discussionmentioning
confidence: 96%
“…In Australia and New Zealand, even more of the decline, around 80% has been attributable to changes in risk factors [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…In their paper, Tobias et al 1 state that dietary trends are less comprehensive and reliable than data on other risk factors but they recognise the possible importance of diet in the decline in CHD mortality in New Zealand. We would like to submit further data on diet in relation to the fall in CHD mortality in Australia and the US.…”
Section: Csiro Human Nutrition/food Science Australiamentioning
confidence: 99%